Hormone therapy with different administration routes for patients with perimenopausal syndrome: a systematic review and network meta-analysis - Liping Wang; Xinrui Luo; Mulan Ren; Yan Wang (Gynecological Endocrinology)
Purpose To comprehensively compare and rank hormone therapy for patients with perimenopausal syndrome.Methods A comprehensive search was conducted on PubMed, Embase, Cochrane Library, Web of Science, CNKI, VIP, and Wanfang databases from inception to August 20, 2024. The quality of the included randomized controlled trials (RCTs) were measured by the Cochrane risk of bias tool. The Grading of Recommendations Assessment, Development and Evaluation (GRADE) method was applied to grade the quality of evidence in this network meta-analysis. Network plots were depicted to show direct and indirect comparisons of hormone therapy for each outcome. The influences of different hormone therapy on the outcomes were illustrated via forest plots and league tables. Rank probabilities showed the ranking of different administration routes.Results Seven studies involving 704 perimenopausal syndrome patients were included. The rank probabilities suggested that oral estradiol (E2) combined with medroxyprogesterone and general health guidance had the highest likelihood to be the optimal therapy for the severity of menopausal syndrome. General health guidance combined with oral E2 was less likely to have a nausea and vomiting, and breast pain.Conclusion Oral E2 and medroxyprogesterone or general health guidance combined with oral E2 may be the effective and safe option for the management of perimenopausal syndrome.